Quand on refuse on dit non d’Ahmadou Kourouma - Arsène Blé Kain (Carnets)
From a socio-semiotic perspective, this article aims to contribute to highlight the presupposed identitarian origins of war in Côte d’Ivoire as described in the posthumous novel of the Ivorian writer Ahmadou Kourouma. Resorting to a literalization of this conflict perceived through a dislocation of the narrative which melts into a fragmented story told in terrible French, Ahmadou Kourouma shows how the concept of “Ivoirité” resulting in excessive quest for a pure Ivorian citizenship threw the country into chaos. Instead of this anthropogenic “Ivoirité-racine”, he advocates for a therapeutic “Ivoirité-rhizome”, a true reflection of a cosmopolitan Côte d’Ivoire.